Potential of Polyisoprenoid of Mangroves as Antimicrobial and Anticancer: A Bibliometric Analysis - Sumardi Sumardi; Masfria Masfria; Mohammad Basyuni; Abdi Wira Septama (Science and Technology Indonesia, 2022)
Mangroves are plants that hope to inhibit coastal abrasion because they can adapt to seawater and withstand beach posture. Poly- isoprenoid compounds contained in mangroves have been known to have an important role in the process of adaptation to seawater salt stress. Publications in the Scopus database were collected using the keywords mangrove, polyisoprenoid, polyisoprene, and dolichol until December 2021. The articles obtained were analyzed bibliometrically using VOSviewer. Totally 129,406 documents were collected with the dominant topics apoptosis and antibacterial activity. Polyisoprenoid appeared 9 times with relevance val- ues 1.1. Polyprenol and dolichol did not link with antibacterial, anticancer, or other biological activities. Several 106,679 (82.5%) are original research articles, 13,907 (10.8%) papers have been published this year (2021). English was mostly used in the language in the publication (95.5%). The countries with the largest publications were the United States, then China, India, Australia, Brazil, United Kingdom, Germany, Japan, France, and Indonesia. The Marine Pollution Bulletin was the most publisher 1,875 documents. Four of the top ten funding sponsors are from China. Wang YS was the main collaborator who has publication links with 50 authors with a total link strength of 32. The field of studies is still in the biological, environmental, social, and pharmaceutical sciences. The study of mangroves and polyisoprenoids related to antimicrobial assays and anticancer increases over time and still needs a lot of scientific studies. Greater research collaboration involving more authors were the hope until the clinic stage.